Keadilan Pembagian Warisan: Perspektif Masyarakat Multikultural - Siregar, Nurma Harana Mora; Azizah, Nur (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2025)
The issue of inheritance distribution in Indonesia is highly relevant in the context of a multicultural society influenced by variations in ethnicity, culture, and religion. This study aims to examine the principles of justice in the distribution of inheritance amidst this diversity. The method employed is library research, focusing on the analysis of literature related to inheritance law, culture, and social impacts. The findings indicate that differences in cultural norms can lead to conflicts in inheritance distribution, even though Islamic law provides clear guidelines. This research recommends the application of maqasid sharia principles and mediation processes to achieve more comprehensive justice within a multicultural society.